LECTURERS’ ADVOCACY ON SOCIAL MEDIA FLATFORMS - Duc, Nguyen Minh; Cuong, Nguyen Duy (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research aims to explore the concept of lecturer advocacy on social media and the motivations behind it. In reviewing 31 papers, the research advocates for all employees to engage as communicators and emphasizes empowering them to utilize social media platforms. Consequently, understanding why employees choose to engage, their methods of participation, and the potential implications is valuable for the case company